Globalization, population flow and the spatial diffusion of COVID-19. Issue 2 (3rd July 2022) - Shen, Jianfa
ABSTRACT : The COVID-19 pandemic has swept the world since December 2019. The spread of COVID-19 has much to do with population flow and close human contacts. This paper demonstrates that the distribution of COVID-19 cases has close relation with the population flow and migration flow in the case of China. Rapid globalization has increased the volumes of migration and travelers in the world since the 1970s. If we reduce the number of air passengers to the level of 0.31 billion in 1970 by 13.6 times in the world, this may delay the same level of infections from being reached by about 3.5 weeks with reduced number of virus export and diffusion. But various authorities may only begin to take systematic and restrictive actions after the case number reaching certain "alarming level", above "saved time" may not be effectively used as the "alarming level" may simply emerge later. The global production network is not able to meet unexpected surging demand of personal protective equipment and other medical essentials in the early stage of pandemic. Emergency plans are need to expand production capacity quickly to deal with future pandemic.